Delineation and characterization of land resources to assess agro-climatic zone based farming situation in Chhattisgarh plains - MANDAL, SAMEER; KHALKHO, DHIRAJ; TRIPATHI, M. P.; DAS, SUSANTA; KUMAR, LOVE (Journal of Soil and Water Conservation, 2022)
The farming situation describes the suitability for cultivation based on the land resources, soil properties and the prevailing slope, and management plan of farming situation emphasising its better understating to stakeholders for efficient natural resources utilisation. The commonly found framing situation classes in Chhattisgarh plains agro-climatic zone are Bhata (Entisols), Matasi (Inceptisols), Dorsa (Alfisols) and Kanhar (Vertisols). The characterization of land resources of Chhattisgarh Plains Agro-climatic Zone based on the farming situation is the main aim of the study. The farming situations are influenced by various parameters such as Normalised Difference Soil Index (NDSI), Land use Land Cover (LULC), soil texture and slope. Analytical Hierarchy Process based Multi-Criteria Decision Making Method (MCDM) was used to calculate the weightage of the parameters and it performed in ArcGIS domain for delineation of farming situations. The overall accuracy and kappa coefficient of the farming situation analysis was found to be 73.09% and 0.64, respectively. The Inceptisols has been found highest in the area about 25625.06 sq. km (33.21%) followed by Entisols 15975 sq. km (21.61%) and Alfisols 14121.26 sq. km (19.10%) area, whereas Vertisols have least in the area with 7658.38 sq. km (10.36%). High potientialis needed for the management in Bhata land followed by Matasi, Dorsa and least in Kanhar soil, which will making it more favourable to farming condition. The study will help the farmer’s community to select the best farming situation and crops for an area and also it will help the policymakers for planning and efficient management of the natural land resources.